Analisis Pengendalian Biaya Food and Beverage Pada Harris Hotel Raya Kuta Bali - I Ketut Gede Budiyasa; Agus Muriawan Putra; Fanny Maharani Suarka (DIPLOMA IV TOURISM PROGRAM STUDY, TOURISM FACULTY,UDAYANA UNIVERSITY, 2018)
The factor that needs to be considered in obtaining the profit from the sale of food and beverages is the cost of food and beverages. The planning of food and beverages cost control at Harris Hotel Raya Kuta was conducted by determining the standard cost percentage that is 32% of total profit for food cost and 22% of total profit for beverages cost, however in its implementation an unfavorable cost deviation always occurred. The purpose of this research was to find out the results of food and beverage cost controlling from January to June 2017, the obstacles and the solution to solve it. The types of data that used in this research were quantitative and qualitative with primer and secondary data sources. The data was collected through observation, interview, library research and documentation. The data were analyzed descriptively quantitatively by using cost calculation formula and descriptively qualitatively analysis. Food and Beverage cost control at Harris Hotel Raya Kuta has not undergoing well, only in April 2017 the cost control of food was able to achieve its standard, it proves that the cost control could be achieve if it was implemented properly. Generally, the increased cost of food and beverage percentage is influenced by high beginning inventory, purchases, store issues. This constraint of cost control was a constraint derived from the function related to the cost control itself, they were the function of purchasing, receiving materials, storage, production and sales functions; on the other hand the effort that should be done is controlling those functions. The suggestion that could be given to Harris Hotel Raya Kuta in controlling the cost of food and beverages is always held function coordinating meeting related to controlling cost, socializing the cost control system and the importance of food and beverages cost control. Furthermore, it is also presenting labor to supervise the development of food and beverages cost control.